Neuro-mechanical adjustments to shod versus barefoot treadmill runs in the acute and delayed stretch-shortening cycle recovery phases. Issue 8 (17th April 2016) - Morio, Cedric; Sevrez, Violaine; Chavet, Pascale; Berton, Eric; Nicol, Caroline
Abstract: In habitually shod recreational runners, we studied the combined influence of footwear and stretch-shortening cycle (SSC) fatigue on treadmill running pattern, paying special attention to neuro-mechanical adjustments in the acute and 2-day delayed recovery periods. The SSC exercise consisted of a series of 25 sub-maximal rebounds on a sledge apparatus repeated until exhaustion. The acute and delayed functional fatigue effects were quantified in a maximal drop jump test. The neuro-mechanical adjustments to fatigue were examined during two submaximal treadmill run tests of 3 min performed either barefoot or with shoes on. Surface electromyographic (EMG) activities, tibial accelerations and kinematics of the right lower limb were recorded during the first and last 15 s of each run. The main result was that neuro-mechanical differences between the shod and barefoot running patterns, classically reported in the absence of fatigue, persisted in the fatigued state. However, in the delayed recovery phase, rearfoot eversion was found to significantly increase in the shod condition. This specific footwear effect is considered as a potential risk factor of overuse injuries in longer runs. Therefore, specific care should be addressed in the delayed recovery phase of SSC fatigue and the use of motion control shoes could be of interest.